Breaking the chain of the advanced sandwich generation through family communication and financial literacy - Kuswanti, Ana; Moenawar, Muhamad Ghozali; Tayibnapis, Radita Gora; Ridwan, Ridwan (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This research aims to analyze the application of communication management in financial literacy to break the chain of continued sandwich generations in the family. The phenomenon of the advanced sandwich generation is increasingly being found in Indonesian society, where individuals not only care for aging parents but also have to bear the economic burden of the next generation. With increasing financial burdens, effective communication within the family is key in managing finances and planning for the future. Research with quantitative and qualitative approaches (explanatory sequential mixed methods) This research explores data by distributing questionnaires to one hundred respondents. It is strengthened by interviews with families identified as the advanced sandwich generation. Then analyze solutions and strategies that can be implemented to improve communication and financial management in the family. Research result shows the importance of communication in financial literacy for generations sandwich. And the need to manage finances sustainably. From focus group discussion produce a model, as a step to break the chain of generations sandwich continuation in the family. The research results also found the main challenges faced by the generation sandwich, such as time and financial pressures, exacerbated by a lack of understanding of good financial management. Finally, this research recommends the importance of increasing financial literacy and managerial skills in communication as keys to supporting generational prosperity sandwich in Indonesia